Improving Regional Economy Through Tourism Industry Optimization (The Case Study of Malang Raya, Indonesia) - Mirza Maulinarhadi Ranatarisza (e-2477-1929)
Malang tourism industry has the potential to be developed. It is because the potential has not been seriously and optimally managed; the management tends to be implemented partially. The greatest potential of the tourism industry identified so far is shopping tourism in Kota Malang, agro tourism and artificial tourist attractions in Batu, and agro tourism in Kabupaten Malang.Optimization on the development of tourism industry in Malang Raya can be done based on the existing situation. Based on the observations, there are several factors affecting the improvement of the economy of local people namely: natural resources, business climate, culture, public facilities, and access to funding. Optimization on the development of the tourism industry must also be based on synergy concept for the three areas involved; thus, the tourism industry of those three areas can grow sinergically and in mutual manner, and support each other. Based on the statistical analyses, it is known that through the support given by the government, the natural resources, business climate, culture, public facilities, and access to funding have significant impact toward increasing the economy of the local people. The results of the study indicate the needs for the government to play such big and important role in the development of tourism industry and in the effort to increase the economy of the people. Keywords: tourism industry, local economy, role of government